Analysis of the spectral behavior of systems with strong antiferromagnetic correlations - Prauchner, Leonardo Costa (2025)
In this study, we explore the impact of short-range antiferromagnetic correlations on the charge density wave (CDW) phase in strongly correlated electron systems exhibiting the pseudogap phenomenon. Our investigation employs an n-pole approximation to consider the repulsive Coulomb interaction (U) and antiferromagnetic correlations. Considering a one-band Hubbard model to account for the Coulomb interaction and a BCS-like model for the CDW order parameter, we observed that an increase in U enhances antiferromagnetic fluctuations, resulting in a flattened re-normalized band around the antinodal point (π,0). The pseudogap manifests itself in the band structure and density of states, prompting exploration of various U and occupation number values. Our findings indicate that antiferromagnetic correlations significantly influence the CDW state, as the Fermi surface is reconstructed within the ordered phase. Furthermore, we found a Lifshitz transition inside both the CDW phase and the normal state, with the latter preceding the onset of the pseudogap. Also, in this work, we investigate the influence of interlayer distance in a heterostructure containing both Kondo effects and short-range magnetic correlations. Our proposed heterostructure comprises three coupled square lattice layers. The first layer is governed by the Kondo-Heisenberg lattice model involving f- and d-electrons, which interact via Kondo and Heisenberg couplings, JK and JH, respectively. The other two layers consist of non-interacting itinerant electrons, where coupling with the first layer is determined by two perpendicular hopping parameters. We find that varying the interlayer couplings induces electronic dynamics at the interface, altering the behavior of mean-field parameters describing the Kondo effect and short-range magnetic correlations. Furthermore, we provide a detailed investigation of electronic properties, including the band structure and Fermi surfaces, offering new insights into the interplay of coupling mechanisms in this class of heterostructures.